Stem cell therapy for single ventricle congenital heart disease – current state and future directions - Bilewska, Agata; Mishra, Rachana; Stefanowicz, Artur; Sharma, Sudhish; Mehta, Vivek; Kaushal, Sunjay (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Hypoplastic left heart syndrome (HLHS) is one of the most complex forms of congenital heart disease, characterized by an underdeveloped left ventricle, outflow tract and aorta. Current surgical and medical treatment for this disease remains palliative. As a result of the multi-step surgery, the right ventricle plays the role of the systemic ventricle, which inevitably leads to its failure. There is an urgent need to develop new treatments to ameliorate the right ventricle failure. Stem cell therapy may represent a new approach to single ventricle pathology. Great numbers of small and large animal studies have proven this therapy to be safe and effective in hypoplastic left heart syndrome. Several clinical trials have been designed to investigate the potential of mesenchymal stem cells in univentricular heart physiology. With increasing evidence, understanding of the mechanism of stem cells’ action has shifted from the concept of differentiation into various heart cell types to paracrine activity playing the major role. The secretome of stem cells has been identified as their functional unit. In this review, we present different types of stem cells used in single ventricle diseases in children as well as their preclinical investigations. We also summarize clinical applications of stem cells in children with HLHS.